PENYIDIKAN TINDAK PIDANA KORUPSI TERHADAP TNI OLEH PENYIDIK KPK - BAHRI YAMIN; FITRIANI AMALIA; SARUDI SARUDI; SAHRUL SAHRUL; FAHRURROZI FAHRURROZI (GANEC SWARA, 2023)
Regarding the polemic regarding the determination of suspects by KPK investigators against active TNI soldiers. The central point is the issue of authority. The authority in question is related to whether or not KPK investigators may carry out investigations and determine suspects against active TNI soldiers. So the researchers proposed a problem formulation; Does the Corruption Eradication Committee have the authority to investigate criminal acts of corruption committed by active TNI while holding civilian positions? The aim to be achieved with this legal issue is to find out and provide scientific information to interested parties. This research is a type of Normative legal research. "According to Peter Mahmud Marzuki, normative legal research is a process of finding legal rules, legal principles and legal doctrines to answer the legal issues faced." The approach is Legislation (Statuta Approach). The analysis is by means of legal interpretation and analytical descriptive. The result is that in a normal view, if the TNI commits corruption while serving as TNI, then it is purely subject to the military justice law. However, if a member of the TNI commits corruption while holding a civil position, then the Corruption Eradication Commission (KPK) investigators have the authority to conduct an investigation based on the provisions of article 42, Law Number 30 of 2002 concerning the Corruption Eradication Commission, Jo, law Number 19 of 2019 concerning the second amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, article 1 number (4), and article 6. Because it is a connectivity court, investigative authority remains with the Corruption Eradication Commission. The Corruption Eradication Commission (KPK) has the authority to coordinate and control the investigation, investigation and prosecution of criminal acts of corruption carried out jointly by persons subject to military justice and general justice.